Haemodynamics Support during Surgical Myocardial Revascularisation in Patients with Systolic Left Ventricular Dysfunction - N. V. Kharitonov; V. V. Vitsukaev; N. A. Trofimov; P. D. Makalsky; V. N. Zavgorodny (Креативная хирургия и онкология)
Coronary heart disease remains a leading cause of death worldwide, and coronary bypass surgery -- the treatment standard in haemodynamically significant multivessel and/or trunk coronary stenosis. Intraoperative haemodynamics support during coronary artery bypass grafting (CABG) in patients with reduced ejection fraction currently remains controversial. Manifold evidence favours CABG with no extracorporeal circulation in higher risk patients to avoid the system’s frequent complications of blood transfusion, renal failure, bleeding, wound infection, cerebrovascular events and humoral disturbances. On the other hand, CABG with extracorporeal circulation and heart arrest allows a bloodless operating field and complete revascularisation in most, often very complex, cases. The complication rate and outcome in beating-heart surgery are reckoned to depend directly on the relevant surgeon’s and clinic experience, which makes many relinquish the technique due to a limited history of skill. This essay overviews the current state of the art, discussions of recent systematic studies on intraoperative haemodynamics support in patients with reduced left ventricular ejection fraction and touches upon the importance of surgeon’s experience for the operation outcome.